Correlations between COMT polymorphism and brain structure and cognition in elderly subjects: An observational study - Cha, Eunsil; Ahn, Hyun Jung; Kang, Wonil; Jung, Kwang-Ik; Ohn, Suk Hoon; Bashir, Shahid; Yoo, Woo-Kyoung (Medicine (Baltimore), 2022)
The catechol-O-methyltransferase (COMT) gene has been noted to play an important role in individual variations in the aging process. We investigated whether COMT polymorphism could influence cognition related to white matter networks. More specifically, we examined whether methionine (Met) allele loading is associated with better individual cognitive performance. Thirty-four healthy elderly participants were recruited; each participant's COMT genotype was determined, and Korean version of Montreal Cognitive Assessment scores and a diffusion tensor image were obtained for all participants. The Met carrier group showed significantly lower mean diffusivity, axial diffusivity, and radial diffusivity values for the right hippocampus, thalamus, uncinate fasciculus, and left caudate nucleus than the valine homozygote group. The Met carrier group also scored higher for executive function and attention on the Korean version of Montreal Cognitive Assessment. Based on these results, we can assume that the COMT Met allele has a protective effect on cognitive decline contributing to individual differences in cognitive function in late life period.